APLIKASI PENGENALAN KEBUDAYAAN JAWA BERBASIS DESKTOP - Adika May Sari; Rina Lestari; Desri Yani; Rosmita Rosmita (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2019)
Nowadays, technology has a big impact for lifes. It also makes children like to use technology to watch videos, play games and socialize through the media. In addition to that technology, they are more familiar with foreign culture compared to their own culture. The habit itself is very related to daily activities using smart phones via the internet. Likewise, the introduction of culture in Java for desktop-based elementary school children is still very rare today. The making of this application is a solution to provide knowledge about diverse cultures in Java. With this application it is hoped that children will get to know their own country's culture more than foreign cultures. Thus, it can create a feeling of love for the nation itself. The desktop application that is served is an application that supports a culture consisting of various menus to facilitate users who open this application with those connected to the internet, using a system development method called waterfall which is system planning, system design, code conversion, system testing and good assistance. In this research, an application in desktop platform was successfully created and from the evaluation it is useful for children and students in learning Java culture.